ANALISISA MINAT BELAJAR SISWA KELAS 6 PADA MATA PELAJARAN BAHASA INDONESIA DI MI MUHAMMADIYAH 1 SUKODADI (Jurnal Ilmiah PENDAS: Primary Educational Journal, 2023)
This study aims to analyze and describe students' learning motivation in learning Indonesian. This type of research is qualitative research. The sample of this research is 31 grade VI students at MI Muhammadiyah 1 Sukodadi.  The data collection methods used were questionnaires, observation, interviews and documentation. Data on student motivation was obtained using a questionnaire sheet. Meanwhile, to support the research data, interviews and classroom observations were conducted. Data analysis was carried out using descriptive qualitative. The questionnaire used is a closed questionnaire, the respondent can only answer with the answer choices provided by the researcher. Respondents cannot provide answers or other responses except those that are available as alternative answers. The results in this study for the first indicator got the highest score of 115 with a percentage of 92%, while for the second indicator the highest score was 87 with a percentage of 70%. There are 5 criteria to see the percentage of students who are interested in learning Indonesian, namely: Very Good, Good, Good Enough, Less Good, and Not Good.
Keywords: interest; learning; Indonesian